A Finding on the Direct Regioselective Cyanation of BODIPY - Gayretli, Cagatay; Teknikel, Efdal; Cinar, Seda; Unaleroglu, Canan (Synlett, 2020)
The first example of direct α-cyanation of a BODIPY core has been achieved on 3-(methoxycarbonyl)ethenyl BODIPY. The structure of α-cyanated BODIPY was confirmed by X-ray analysis. Further cyanation took place on the meso-carbon of BODIPY.
Keywords: BODIPY; cyanation; nucleophilic aromatic substitution; hydrogen substitution; regioselective substitution